2017
DOI: 10.22500/sodality.v5i2.17975
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Migrant Workers from Upstream to Downstream through “Peduli Buruh Migran” Villages (Desbumi): Study at Kuripan Village, Central Java and Nyerot Village, West Nusa Tenggara

Abstract: <p>ABSTRACT<br />The high Number of Indonesian migrant workers (IMWs)workingin abroad, in facts, is not supported by adequate government protections. Due to BNP2TKI Crisis Center data of 2016, there are at least 27 thousand casesfaced by IMWs working in many countries all over the world. According to the research results conducted Wulan (2011), problems faced by IMWs in the destination countries, 80 percent of those come from villages. A village actually has strategic roles to becomes a foundation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In addition, Saleh (2015) has shown that social relations among migrants and between migrants and local residents must be well established to ensure security and comfort in entrepreneurship to achieve sustainable livelihoods. This means that policy and institutional aspects are essential in maintaining a livelihood by migrants (Wulan et al, 2017;Soeliongan, 2017).…”
Section: Conceptual Framework Of Sustainable Livelihoodsmentioning
confidence: 99%
“…In addition, Saleh (2015) has shown that social relations among migrants and between migrants and local residents must be well established to ensure security and comfort in entrepreneurship to achieve sustainable livelihoods. This means that policy and institutional aspects are essential in maintaining a livelihood by migrants (Wulan et al, 2017;Soeliongan, 2017).…”
Section: Conceptual Framework Of Sustainable Livelihoodsmentioning
confidence: 99%